2021
DOI: 10.1038/s41386-021-00964-0
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant treatment ameliorates prefrontal hypomyelination and cognitive deficits in a rat model of schizophrenia

Abstract: Cognitive dysfunction in schizophrenia (SZ) is thought to arise from neurodevelopmental abnormalities that include interneuron hypomyelination in the prefrontal cortex (PFC). Here we report that RNA-sequencing of the medial (m)PFC of the APO-SUS rat model with SZ-relevant cognitive inflexibility revealed antioxidant metabolism as the most-enriched differentially expressed pathway. Antioxidant-related gene expression was altered throughout postnatal development and preceded hypomyelination. Furthermore, reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 44 publications
(81 reference statements)
1
12
0
Order By: Relevance
“…Maas and colleagues, using apomorphine-susceptible (APO-SUS) rat model to study schizophrenia, reported a central role for GSH antioxidant metabolism. They found that treatment with the GSH precursor N -acetylcysteine (NAC) restored not only GSH metabolism but also improved mPFC hypomyelination and cognitive functioning of APO-SUS rats [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Maas and colleagues, using apomorphine-susceptible (APO-SUS) rat model to study schizophrenia, reported a central role for GSH antioxidant metabolism. They found that treatment with the GSH precursor N -acetylcysteine (NAC) restored not only GSH metabolism but also improved mPFC hypomyelination and cognitive functioning of APO-SUS rats [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…This large body of evidence has led to the claim that various mechanistic strands underlying schizophrenia converge on the “hub of oxidative stress” indexed by GSH [ 48 , 49 ]. Preclinical models with early GSH deficit (i.e., from postnatal day 0 onwards) display various schizophrenia-like features in adult life, including a sensitivity to dopamine excess [ 50 ], and prefrontal hypomyelination [ 51 ]. Nevertheless, chronic peri-adolescent treatment with the glutathione precursor N-acetylcysteine (postnatal days 5–90) restores antioxidant-related and myelin-related mRNA expression improving cognitive flexibility in later life [ 51 ].…”
Section: Glutathione In Schizophreniamentioning
confidence: 99%
“…Preclinical models with early GSH deficit (i.e., from postnatal day 0 onwards) display various schizophrenia-like features in adult life, including a sensitivity to dopamine excess [ 50 ], and prefrontal hypomyelination [ 51 ]. Nevertheless, chronic peri-adolescent treatment with the glutathione precursor N-acetylcysteine (postnatal days 5–90) restores antioxidant-related and myelin-related mRNA expression improving cognitive flexibility in later life [ 51 ]. Thus, despite the likely developmental origins of the GSH-deficit, a phenotype ‘rescue’ is possible in preclinical models with interventions in later life.…”
Section: Glutathione In Schizophreniamentioning
confidence: 99%
“…Preclinical models with early GSH deficit (i.e. from postnatal day 0 onwards) display various schizophrenia-like features in adult life, including a sensitivity to dopamine excess [50], and prefrontal hypomyelination [51]. Nevertheless, chronic peri-adolescent treatment with the glutathione precursor N-acetylcysteine (postnatal days 5-90) restores antioxidant-related and myelin-related mRNA expression improving cognitive flexibility in later life [51].…”
Section: Glutathione In Schizophreniamentioning
confidence: 99%
“…from postnatal day 0 onwards) display various schizophrenia-like features in adult life, including a sensitivity to dopamine excess [50], and prefrontal hypomyelination [51]. Nevertheless, chronic peri-adolescent treatment with the glutathione precursor N-acetylcysteine (postnatal days 5-90) restores antioxidant-related and myelin-related mRNA expression improving cognitive flexibility in later life [51]. Thus, despite the likely developmental origins of the GSH-deficit, a phenotype 'rescue' is possible in preclinical models with interventions in later life.…”
Section: Glutathione In Schizophreniamentioning
confidence: 99%